2020
DOI: 10.28969/ijeir.v10.i1.r6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drugs used in general anesthesia on oocyte and embryo quality in Iraqi infertile females undergoing intracytoplasmic sperm injection

Abstract: Various types of anesthetic techniques were described for oocyte recovery. Different anesthetic agents have been used with different effects on oocyte quality and embryonic development and studies on the potential toxicity of general anesthesia ended up with conflicting results. Many experiments as well as human studies documented the existence of anesthetic agents in the follicular fluid (FF) with possible adverse effects on the oocyte quality and subsequent embryo development. Ketamine and remifentanil were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Also, Mohsen et al study found that abnormal oocyte rate was 6-14% (9) . Another study from Iran conducted by Farzi et al in 2019 reported a mean number of retrieved oocytes of 10.3 (10) .…”
Section: Discussionmentioning
confidence: 97%
“…Also, Mohsen et al study found that abnormal oocyte rate was 6-14% (9) . Another study from Iran conducted by Farzi et al in 2019 reported a mean number of retrieved oocytes of 10.3 (10) .…”
Section: Discussionmentioning
confidence: 97%
“…They concluded that remifentanil was superior to ketamine where significantly higher fertilization rate has been reported in remifentanil group than ketamine group, however, they did not find significant difference between both groups in the cleavage rates but the positive pregnancy rates was significantly higher in rem-ifentanil group than ketamine group, 46.7% vs. 20%, respectively. On the other hand, the Iraqi study documented that the time of procedure was not significantly different but the recovery time was longer in ketamine group than remifentanil, therefore, Mohsin et al concluded that remifentanil was superior to ketamine in in ICSI proce-dures due to high rates of fertilization and positive pregnancy with shorter recovery time (12) From other point of view, a double-blind clinical trial conducted in Turkey by Sarikaya et al, compared the effect of two different doses of remifentanil infusion, 0.1 mcg/kg/min and 0.15 mcg/kg/min infusion for sedation during IVF procedures among 86 ASA I-II grade women aged 18-40 years managed with IVF procedures. Sarikaya et al assessed vital signs total required doses of remifentanil, fertilization rate, cleavage rate and pregnancy rates and all these rates were not significantly different between the two groups however, the anesthesiologist satisfaction was higher with lower dose of remifentanil while surgeon satisfaction was higher in the second group with higher dose of remifentanil, but patients satisfaction was good in both groups.…”
Section: Positive Pregnancy Negative Pregnancymentioning
confidence: 98%